2017
DOI: 10.1016/j.acvd.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, aetiological spectrum and management of valvular heart disease in a Tunisian cardiovascular centre

Abstract: This retrospective study has shown that the main cause of valvular heart disease in Tunisia is rheumatic fever. Mitral stenosis and multiple valve disease are the most frequent valvular heart diseases in Tunisia. Percutaneous mitral balloon valvuloplasty and prosthetic valve replacement are the preferred treatment methods for valvular heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
13
2
Order By: Relevance
“…Whereas congenital heart disease is more common in Europe and North America, rheumatic disease predominates in other parts of the world, particularly those that are underrepresented in the STS-CHSD. 2,12,13 A 2009 AVR study from Saudi Arabia demonstrated 58% of patients had rheumatic AV pathology, compared with 0.5% in the current study. 2 Likewise, the proportion of patients with connective tissue disorders such as Marfan syndrome influences valve choice.…”
Section: Valve Choicecontrasting
confidence: 43%
“…Whereas congenital heart disease is more common in Europe and North America, rheumatic disease predominates in other parts of the world, particularly those that are underrepresented in the STS-CHSD. 2,12,13 A 2009 AVR study from Saudi Arabia demonstrated 58% of patients had rheumatic AV pathology, compared with 0.5% in the current study. 2 Likewise, the proportion of patients with connective tissue disorders such as Marfan syndrome influences valve choice.…”
Section: Valve Choicecontrasting
confidence: 43%
“…In fact, pregnancy period is characterized by an increase of cardiac output brought by increased heart rate and stroke volume, and oppositely a decrease of peripheral resistance by a peripheral vasodilatation. The drop of vascular resistance explains the tolerance of regurgitant lesions [6,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation (WHO) considers severe stenotic valve heart disease as a contraindication to conception (WHO IV category) [5]. Giving that rheumatic heart disease remains prevalent in our country [6], managing pregnant women with such conditions is still encountered in our daily practice and is a challenging situation for obstetricians, cardiologists and anaesthesiologists. In fact, we have to deal with two main challenges; the rst one is: should we opt for stopping the pregnancy considering maternal and foetal risks.…”
Section: Introductionmentioning
confidence: 99%
“…In fact during pregnancy there will be an increase of cardiac output brought by increased heart rate and stroke volume, and oppositely a decrease of peripheral resistance by a peripheral vasodilatation. The drop of vascular resistance explains the tolerance of regurgitant lesions (6,(24)(25)(26).…”
Section: Cardiac Adverse Eventsmentioning
confidence: 99%
“…The World Health Organisation considers severe stenotic valve heart disease as a contraindication to conception (WHO IV category) (5). Giving that rheumatic heart disease remains prevalent in our country (6), managing pregnant woman such conditions is still encountered in our daily practice and is a challenging situation for obstetricians, cardiologists and anaesthesiologists. We have to deal in this situation with two main challenges; rst should we advise to stop the pregnancy taking in consideration the maternal and foetal risk.…”
Section: Introductionmentioning
confidence: 99%